Morphological integration of the canine region within the hominine alveolar arch. Issue 154 (May 2021) - Lawrence, Julie; Kimbel, William H.
Abstract: The early hominin record is characterized by numerous shifts in dental proportions (e.g., canine reduction and megadontia) linked to changes in diet and social behavior. Recent studies suggest that hominins exhibit a reduction in the magnitude of covariation between the anterior and posterior dental components compared with other extant great apes. They point toward, but do not directly test, the relative independence of canine morphology within the hominin alveolar arch. This study focuses specifically on the how the canine region covaries with other regions of the dental arch because the canine region has drastically reduced in size and changed in shape across human evolution. We examine extant primate species most commonly used as a comparative framework for fossil hominin morphology: Gorilla gorilla ( n  = 27), Pan troglodytes ( n  = 27), and Homo sapiens ( n  = 30). We used geometric morphometric methods to test for size and shape covariation between the canine region with other dental regions. We also examined the influence of sexual dimorphism and allometry on intraspecific and interspecific patterns of covariation. The analysis of size and shape covariation between the mandibular canine and other individual tooth regions elucidated complex, species-specific, and sex-specific morphological relationships in the mandibular alveolar arch. There was little evidence to support different patterns of morphological integration between humans on the one hand and nonhuman apes on the other. Canine region morphology was relatively independent from other dental regions across species based on shape and did not significantly covary more with either the incisor or postcanine region in any species. The size correlations between the canine and other dental regions were moderate to high. The species-specific results of this study question the ability to make a priori assumptions about morphological integration in the extant hominin mandibular alveolar arch and its application to the fossil record.